Analisis Physical Evidence pada Rumah Sakit Hermina Pasteur Bandung - Ida Jalilah Fitria; Indri Srikandi Sutisna (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2022)
Abstract During the Covid-19 Pandemic, the hospital is certainly one of the institutions that is highly highlighted by the community, every activity and service carried out is always a benchmark for the success of the hospital in handling patient satisfaction, including facilities and infrastructure that are considered adequate by the patient. The sampling technique in this study is the survey method. Meanwhile. The analytical technique used is the descriptive analysis method. Respondents taken are visitors to Hermina Pasteur Hospital. This method is done by distributing questionnaires/questionnaires, documentation and interviews with sampling using iterations totaling 80 respondents. The CE on the dimensions of the Facility Exterior, Facility Interior and Other Tangible elements are in medium condition, meaning that the Facility Exterior, Facility Interior and Other Tangible elements owned by Hermina Pasteur Hospital are quite good. Abstrak Pada saat Pandemi Covid-19, Rumah Sakit tentu menjadi salah satu institusi yang sangat disoroti oleh masyarakat, setiap aktivitas dan pelayanan yang dilakukan selalu menjadi tolak ukur keberhasilan Rumah Sakit dalam menangani Kepuasan Pasien tidak terkecuali sarana dan prasarana yang dianggap telah memadai oleh pasien. Teknik pengambilan sampel pada penelitian ini yaitu metode survei. Sedangkan, tehnik analisis yang digunakan menggunakan metode analisis deskriptif Responden yang diambil yaitu adalah pengunjung Rumah Sakit Hermina Pasteur cara ini dilakukan dengan menyebarkan kuesioner / angket, dokumentasi dan wawancara dengan pengambilan sample menggunakan iterasi yang berjumlah 80 Responden. Hasil penelitian Kondisi Physical Evidence pada dimensi Facility Exterior, Facility Interior and Other Tangible elements berada dalam kondisi Sedang berarti bahwa Facility Interior, Facility Exterior dan Tangible Element yang dimiliki Rumah Sakit Hermina Pasteur sudah cukup baik.